APPLICATION OF THE STAD TYPE COOPERATIVE LEARNING MODEL TO IMPROVE STUDENTS MATHEMATICS LEARNING OUTCOMES - Anik Dwi Febrianti; Agung Setyawan (Citra Dharma Cindekia, 2022)
This classroom action research aims to improve the learning outcomes of FPB and Mathematics KPK materials for fourth grade students at SDN Patranrejo Berbek through the STAD model. Data collection techniques used are interviews, questionnaires, written tests, and documentation, with data analysis techniques in the form of quantitative qualitative data analysis. The results showed an increase in the results of observations of teacher activities and student activities. In cycles I and II, the results of teacher activity observations increased from 83% to 92%. In the observation of student activity, which increased from 83% to 94% in cycle II. The average score of students at the time of pretest and posttest also increased. In the first cycle the students' pretest results increased to 70% in the posttest to 79%, while in the second cycle the students' pretest results increased from 81% to 84%. Likewise, the students' mastery results increased. In the first cycle, the students' mastery results in the pretest were 30% and increased at the posttest to 69%. In cycle II, the results of completeness on the pretest were 86% to 95%. In conclusion, the STAD type of cooperative learning model in class IV SDN Patranrejo can improve student learning outcomes in Mathematics FPB and KPK.